The Controlling Aedes Aegepty Mosquitoes as Dengue Fever Vectors Using 3M Poster Media for Junior High School Students of the Mutiara Aulia Education Foundation (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is still a serious health problem in Indonesia, with 210,644 cases and 1,239 deaths reported until the 43rd week of 2024. One of the causes is the activity of disease vectors that bite in the morning and afternoon which can occur when children are at school. This study aims to determine the effect of counseling on increasing students' knowledge about prevention and control of DHF disease vectors at Mutiara Aulia Middle School. This study used an experimental method with a Pre- Experimental (non-designs) design of the One-Group Pretest-Posttest Design . The study population was all students of Mutiara Aulia Middle School with a sample of 63 people. Based on the research that has been carried out, the results found that the average pre-test was 52.42 and the average post-test was 80.06, which means that there was an increase in knowledge. The results also show that the significance value is 0.000 (